2017
DOI: 10.1039/c7ra05379g
|View full text |Cite
|
Sign up to set email alerts
|

Selenoprotein SelK increases the secretion of insulin from MIN6 β cells

Abstract: The expression of selenoprotein SelK triggers the secretion of insulin from MIN6 β cells by increasing the cytosolic free Ca2+ level, resulting from the up-regulated IP3R3 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…This is in line with data showing that selenite induced insulin expression in vitro and release in islets of Langerhans [22]. Mechanistic insights are missing but this might relate to altered SelenoK expression, which regulates insulin secretion in Min6 cells [35]. Alternatively, increased pancreatic but unchanged circulating insulin levels might suggest increased insulin degradation via insulindegrading enzyme (IDE).…”
Section: Discussionsupporting
confidence: 83%
“…This is in line with data showing that selenite induced insulin expression in vitro and release in islets of Langerhans [22]. Mechanistic insights are missing but this might relate to altered SelenoK expression, which regulates insulin secretion in Min6 cells [35]. Alternatively, increased pancreatic but unchanged circulating insulin levels might suggest increased insulin degradation via insulindegrading enzyme (IDE).…”
Section: Discussionsupporting
confidence: 83%
“…Meng et al . have found that selenoprotein K modulates the expression of inositol trisphosphate receptor type 3, thereby influencing intracellular Ca 2+ levels and insulin release . Recently, Se has been found to have potential for improving insulin resistance and increasing insulin sensitivity .…”
Section: Discussionmentioning
confidence: 99%
“…Selk, which is located in ER and plasma membrane, is a newly identified selenoprotein, which may be required for normal development but does not reveal changes in the total antioxidant status of embryos and cells [61]. Furthermore, a recent study suggested that the expression of Selk may increase the secretion of insulin in the endoplasmic reticulum (ER) [62]. Selk might increase lipid consumption in the liver and then suppress NAFLD and NASH.…”
Section: Discussionmentioning
confidence: 99%